The effects of immunomodulation by macrophage subsets on osteogenesis in vitro. Issue 1 (December 2016) - Loi, Florence; Córdova, Luis; Zhang, Ruth; Pajarinen, Jukka; Lin, Tzu-hua; Goodman, Stuart; Yao, Zhenyu
Abstract Background Bone formation and remodeling are influenced by the inflammatory state of the local microenvironment. In this regard, macrophages are postulated to play a crucial role in modulating osteogenesis. However, the differential effects of macrophage subsets and their plasticity on bone formation are currently unknown. Methods Polarized primary murine macrophages and preosteoblastic MC3T3 cells were co-cultured to investigate the effect of non-activated M0, pro-inflammatory M1, and tissue-regenerative M2 macrophages on the osteogenic ability of MC3T3-E1 cellsin vitro . Furthermore, to model the physiological transition from inflammation to tissue regeneration, M1-MC3T3 co-cultures were treated with interleukin-4 (IL-4) at different time points to modulate the M1 phenotype towards M2. Macrophage phenotypic markers were assessed by flow cytometry and enzyme-linked immunosorbent assay. A time course study of osteogenic markers at different time points was conducted: alkaline phosphatase (ALP) mRNA levels were evaluated at week 1, ALP activity and osteocalcin and osteopontin mRNA levels at week 2, and matrix mineralization and osteocalcin and osteopontin protein concentrations at week 3. Supernatant collected 72 hours after seeding or IL-4 treatment, whichever was later, was analyzed for oncostatin M, a cytokine released by macrophages that has been recognized to enhance osteogenesis. Unpaired t test or one-way ANOVA with Tukey's or Dunnett's post hoc tests were used for statistical comparison of the groups. Results Co-culture with any of the macrophage subtypes increased the osteogenic ability of MC3T3 cells as indicated by increases in ALP activity and matrix mineralization. Increased ALP activity, osteocalcin concentration, and matrix mineralization demonstrated that osteogenesis by M1-MC3T3 co-cultures was further enhanced by macrophage phenotype modulation to M2 via IL-4 treatment 72 hours after seeding. Increased oncostatin M protein concentration in untreated M1-MC3T3 co-cultures and M1-MC3T3 co-cultures treated with IL-4 at 72 hours correlated with greater ALP activity and matrix mineralization. Conclusions These results suggest that a transient inflammatory phase is crucial for enhanced bone formation. Macrophage plasticity may offer new strategies for modulating the local inflammatory microenvironment with the aim of potentially enhancing bone repair.